Prasugrel Use Following PCI and Associated Patient Outcomes: Insights From the National VA CART Program. Issue 10 (October 2016) - Aggarwal, Vikas; Armstrong, Ehrin J.; Liu, Wenhui; Maddox, Thomas M.; Ho, P. Michael; Carey, Evan; Wang, Tracy; Sherwood, Matthew; Tsai, Thomas T.; Rumsfeld, John S.; Bradley, Steven M.
ABSTRACT: Background: Prasugrel is more effective than clopidogrel in preventing thrombotic complications after percutaneous coronary intervention (PCI) among patients with acute coronary syndromes (ACS), but it increases the risk of bleeding in subgroups of patients. There is limited data on whether prasugrel use in routine practice is targeted to clinical settings with greatest anticipated patient benefit. Methods: In a national cohort of 11 617 veterans who underwent PCI between 2010 and 2013 at Veterans Administration hospitals nationwide, we assessed overall trends in the use of prasugrel and the frequency of prasugrel use in patients with contraindications (prior transient ischemic attack or cerebrovascular accident), higher bleeding risk (age ≥75 or weight <60 kg), and nonindicated settings (non–acute coronary syndrome [non‐ACS]). We then evaluated the association between prasugrel use and 1‐year risk‐adjusted mortality, myocardial infarction, and major bleeding rates. Results: Overall, 1040 (9.0%) patients who received prasugrel after PCI were included. Prasugrel was infrequently used in contraindicated (2.4%) or higher‐bleeding‐risk (1.8%) settings. Additionally, 35.8% of patients received prasugrel in settings that lack evidence of clinical benefit (ie, non‐ACS). Compared with clopidogrel, there were no significant differences in risk‐adjusted mortality, myocardial infarction, or major bleeding outcomes with prasugrel therapy at 1‐year follow‐up. Conclusions: Prasugrel use after PCI in the Veterans Administration is low and prasugrel was rarely used in contraindicated or high‐bleeding‐risk settings. However, a third of patients received prasugrel for off‐label non‐ACS indications that lack efficacy data.